Beyond Typical Shingles: Trigeminal Herpes Zoster Accompanied by Severe Penile Neuropathic Pain: A Case Report - Kaoru Obata; Masako Kinoshita; Mai Yoshioki; Takuro Sunada; Katsuro Shindo (International Journal of Infectious Diseases)
Background: Varicella-Zoster virus (VZV) can be reactivated to cause herpes zoster and associated with various neurological manifestations including meningitis. We report a case of penile neuropathic pain that occurred simultaneously with trigeminal herpes zoster. Case Description: A 31-year-old male presented with abnormal sensations and pain in the perineum, glans penis and bilateral posterior thighs for nine months since he developed right trigeminal herpes zoster. Although no rash appeared on his genitalia, he experienced a sense of residual urine, difficulty urinating, and tingling sensations in the perineum and bilateral posterior thighs when sitting. During the first week of herpes zoster onset, after sitting for two hours in a long meeting, the patient experienced sharp, shooting neuropathic pain on the dorsal side of the glans penis, leading to a vasovagal reflex syncope requiring ambulance transport. He had no fever or headache suggestive of meningitis throughout the entire course. At the first visit to our neurology clinic, general physical and neurological examinations were unremarkable without rash, sensory loss or dysesthesia. Blood test findings were consistent with a previous VZV infection. Pelvic MRI showed no organic lesions. Due to the symptoms being provoked by sitting or perineal compression, a donut cushion was recommended. With the use of the cushion, along with pregabalin and vitamin B12, the sharp penile pain subsided, and the tingling sensation that appeared when sitting gradually resolved. All symptoms improved fifteen months after onset without the need for continued medication. Discussion: The distribution of dysesthesia included the bilateral posterior thighs, suggesting that the site of lesion was not the pudendal nerves but rather more central, such as the nerve roots of the bilateral lumbosacral regions and the lower spinal cord. In cases of VZV meningitis, even without a rash on the genitalia, there have been reports of urinary symptoms, known as meningitis-retention syndrome, which can be caused by trigeminal herpes zoster. Additionally, it is known that VZV infection can lead to cerebrospinal fluid pleocytosis even in the absence of meningitis. Although the cerebrospinal fluid was not examined in this case, his neurological symptoms could have been caused by a condition similar to meningitis-retention syndrome. The neuropathic pain in the penis and the associated dysesthesia around the perineum first appeared and reached peak severity with the onset of herpes zoster. These symptoms then progressively lessened over fifteen months. This clinical course suggests that these genitourinary symptoms can be considered neurologic complications related to the reactivation of VZV. Conclusion: This case underscores the need to consider VZV reactivation as a potential cause of unusual penile neuropathic pain, even when the typical rash is absent on the penis. A donut cushion may be effective when dysesthesia in the perineal area worsens while sitting.